Some Theoretical Aspects of Juvenile Sexual Assaults - BAZARLINOVA, Ardak U.; MARAT, Aigul M. (Journal of Advanced Research in Law and Economics; Vol 9 No 1 (2018): JARLE Volume IX Issue 1(31) Spring 2018, 2018)
This article is concerned with the peculiarities of criminal liability for juvenile sexual assaults in the legislation of the Republic of Kazakhstan. We consider the theoretical and legal aspects of the legal protection of minors and provide the criminal-legal characterization of juvenile sexual crimes. We also suggest the classification of sexual crimes distinguishing its criteria. We determine the age features of minors as an object of legal protection. While studying the opinion of leading scholars in the field of criminal law and criminology, we have outlined the main directions of scientific research related to the above-mentioned problem. Based on the survey of theoretical issues and the criminal legislation of the Republic of Kazakhstan and based on the scientific research of domestic scholars, we have defined a specific list of unlawful acts infringing the sexual freedom and sexual inviolability of minors embodied in the existing Criminal Code of the Republic of Kazakhstan. In addition, within the framework of the study, we have concluded that the theoretical aspects of juvenile sexual assaults are urgent and need to be further analyzed. We believe that the theoretical study of this problem will make it possible to further improve the criminal legislation and prevention of these types of crimes.